Effects of the maternal and child health handbook and other home-based records on mothers’ non-health outcomes: a systematic review - Akira Shibanuma; Masamine Jimba; Rogie Royce Carandang; Jennifer Lisa Sakamoto; Ekaterina Yarotskaya; Milana Basargina; Mika Kondo Kunieda (BMJ Open)
Objective This review aimed to investigate the effects of the maternal and child health (MCH) handbook and other home-based records on mothers’ non-health outcomes.Design Systematic review.Data sources PubMed, Web of Science, CINAHL, Academic Search Complete, PsycArticles, PsycINFO, SocINDEX, CENTRAL, NHS EED, HTA, DARE, Ichuushi and J-STAGE through 26 March 2022.Eligibility criteria for selecting studies Original research articles examining home-based records and mothers’ non-health outcomes published in English or Japanese across various study designs.Data extraction and synthesis Two independent reviewers extracted relevant data and assessed the risk of bias. We assessed the certainty of evidence for each study using the Grading of Recommendations Assessment, Development, and Evaluation approach. Due to the heterogeneity of the included studies, we conducted a narrative synthesis of their findings.Results Of the 4199 articles identified, we included 47 articles (20 in Japanese) in the review. Among the different types of home-based records, only the MCH handbook provided essential information about the mother–child relationship, and its use facilitated the mother–child bonding process. Mothers reported generally feeling satisfied with the use of home-based records; although their satisfaction with health services was influenced by healthcare providers’ level of commitment to using these records. While home-based records positively affected communication within the household, we observed mixed effects on communication between mothers/caregivers and healthcare providers. Barriers to effective communication included a lack of satisfactory explanations regarding the use of home-based records and personalised guidance from healthcare providers. These records were also inconsistently used across different health facilities and professionals.Conclusions The MCH handbook fostered the mother–child bond. Mothers were generally satisfied with the use of home-based records, but their engagement depended on how these records were communicated and used by healthcare providers. Additional measures are necessary to ensure the implementation and effective use of home-based records.PROSPERO registration number CRD42020166545.